Robuvit®: improvement of fatigue in medical convalescence - Ippolito, Edmondo; Belcaro, Gianni; Luzzi, Roberta; Hosoi, Morio; Dugall, Mark; Rohdewald, Peter; Feragalli, Beatrice; Cotellese, Roberto; Peterzan, Paula (The Journal of sports medicine and physical fitness, 2018)
The aim of this registry study was the evaluation of symptoms of fatigue following supplementation with an oak wood extract (Robuvit®) after disappearance of acute symptoms. Robuvit®, with established antioxidant-antifatigue activity, has been successfully used in hepatic failure and in chronic fatigue syndrome: these conditions are characterized by weakness and fatigue and are broadly comparable to convalescence that is associated to increased oxidative stress. The registry study lasted 3 weeks. After a period (7-10 days) of flu, during the post-disease period (3 days without disease) subjects were included into the study. One group of subjects was supplemented with Robuvit® (300 mg/day) in addition to a standard management (SM) plan, another group of patients was treated with the standard management only. The SM and the supplement group were comparable in all convalescence parameters at inclusion. Weakness and heart rate were significantly reduced with Robuvit® in comparison with the controls (P<0.05) at 10 days and at 3 weeks; Attention and sleep patterns improved significantly at 3 weeks with Robuvit® (P<0.05) in comparison to controls. Recovery after efforts was normalized at 10 days in the supplement group, significantly better versus controls (P<0.05). O2 saturation increased significantly with Robuvit® at 10 days in comparison to controls (P<0.05). The alterations in working/concentration capacity were better improved with the supplement (P<0.05). Oxidative stress was significantly decreased (P<0.05) in comparison to controls. The improvement of health according to the Karrnofsky Scale was significantly more pronounced in the Robuvit® group (P<0.05). The supplement was well tolerated. The causative relations between Robuvit® supplementation, oxidative stress, vigor and fatigue in convalescence need more specific evaluations in a larger number of subjects. This preliminary study may indicate a possible supplementation in convalescence.